'Micro‐managers' of hepatic lipid metabolism and NAFLD. (21st July 2015) - Liu, Wei; Cao, Hongchao; Yan, Jun; Huang, Ruimin; Ying, Hao
Abstract : Nonalcoholic fatty liver disease (NAFLD) is tightly associated with insulin resistance, type 2 diabetes, and obesity. As the defining feature of NAFLD, hepatic steatosis develops as a consequence of metabolic dysregulation of de novo lipogenesis, fatty acid uptake, fatty acid oxidation, and triglycerides (TG) export. MicroRNAs (miRNAs), a class of endogenous small noncoding RNAs, play critical roles in various biological processes through regulating gene expression at post‐transcriptional level. A growing body of evidence suggests that miRNAs not only maintain hepatic TG homeostasis under physiological condition, but also participate in the pathogenesis of NAFLD. In this review, we focus on the current knowledge of the hepatic miRNAs associated with the development of liver steatosis and the regulatory mechanisms involved, which might be helpful to further understand the nature of NAFLD and provide a sound scientific basis for the drug development. WIREs RNA 2015, 6:581–593. doi: 10.1002/wrna.1295 This article is categorized under: RNA in Disease and Development > RNA in Disease